Late Gothic churches of the Wielun type – the problem of identification, genetic and settlement determinants and present contemporary cultural values - Figlus, Tomasz (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The chapter concerns the problem of identification, genetic and settlement conditions, and present cultural values of late Gothic wooden churches representing the Wielun type. It is a homogeneous collection from the sixteenth century, specific in terms of location and physiognomy. As a result of the discussion on the classification criteria, 10 preserved objects of this type were identified. Based on historical sources and literature, an analysis of the origins of the studied group of historic buildings was carried out, taking into account the issues of church administration, settlement and ownership relations. Then, the location and architectural features of the churches were examined, taking into account the variability and preservation of historic structural and decorative forms. The analyzed objects are characterized by outstanding cultural values and therefore require special care and implementation of complex actions in the field of legal protection and conservation.